Feasibility, effectiveness and safety of self-management in pulmonary rehabilitation: a study protocol using a hybrid type 1 effectiveness-implementation design - Ricke, Ellen; Dijkstra, Arie; Bakker, Eric W. (Frontiers in Rehabilitation Sciences, 2023)
Background: As population ageing accelerates worldwide, chronic diseases will place an increasing burden on society and healthcare systems. Self-management interventions may become a key strategy for addressing chronic disease burden and healthcare costs, also in pulmonary rehabilitation (PR). One of the challenges here is long-term adherence. Understanding the level of adherence to PR may help inform clinical decision-making to focus more on self-management and less on clinical supervision. For this reason, a prediction model (PATCH) was developed. The presented protocol concerns a study that aims 1. to evaluate the safety and effectiveness of self-management within pulmonary rehabilitation (PR) on health outcomes in patients with chronic obstructive pulmonary disease (COPD), 2. to evaluate the predictive validity of the PATCH tool, and 3. to evaluate feasibility and acceptability of self-management and the PATCH tool by patients and physiotherapists. Methods and analysis: This is a protocol of a hybrid type 1 effectiveness-implementation design, performed in primary physiotherapy practices in The Netherlands. The aim is to include 108 patients with COPD who have already followed PR for at least six weeks (maintenance stage of PR). According to the Dutch KNGF Guideline COPD, physiotherapists should reduce the number of supervised treatments after the maintenance phase and support self-management. In practice, this does not (always) happen. This protocol is based on implementing guideline advice: clinical supervision will be halved but patients are stimulated to engage in self-management by exercising unsupervised, leading to no change in the total planned exercise frequency. During the supervised sessions physiotherapists will assess and stimulate self-management. At baseline, and after 3, 6, 9 and 12 months, health outcomes (including adherence) will be evaluated as the primary outcome of this study. At each measurement, the physiotherapist will decide on the basis of individual scores whether the patient needs more clinical supervision or not. Secondary outcomes are the discriminatory power of the PATCH tool (can patients be correctly classified as adherent or non-adherent), and feasibility and acceptability of self-management and the PATCH tool by patients and physiotherapists. Questionnaires and semi-structured interviews will be used for assessment of the outcomes. Trial registration number: METc 2023/074.